2020
DOI: 10.1016/j.clgc.2019.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Utilization and Outcomes of Surgical Castration in Comparison to Medical Castration in Metastatic Prostate Cancer

Abstract: Androgen deprivation therapy is the gold standard for metastatic prostate cancer, which can be achieved either by surgical or medical castration. In this study of 33,585 patients in the National Cancer Database, there was significant decline in the trend of utilization of surgical castration from 8.6% in 2004 to 3.1% in 2014. However, there was no survival difference with surgical castration when compared with medical castration. Increasing the utilization of surgical castration could help reduce health care e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 22 publications
(21 reference statements)
1
25
0
Order By: Relevance
“…Although a series of treatments for PC, including surgical castration, androgen deprivation therapy (ADT), and chemotherapy and radiation therapy [ 2 ], have been significantly refined and improved in recent years, the 5-year relative survival rates for PC by stage at diagnosis and race have reached 98% among the selected cancer types [ 1 ]. Repeated use of single therapeutic agents may lead to undesirable and severe adverse effects; for example, most patients have difficulty accepting surgical castration therapy [ 3 , 4 ]. Worse still, with the development of the disease, ADT causes almost all patients to become less sensitive to androgens and progress to castration-resistant prostate cancer (CRPC) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although a series of treatments for PC, including surgical castration, androgen deprivation therapy (ADT), and chemotherapy and radiation therapy [ 2 ], have been significantly refined and improved in recent years, the 5-year relative survival rates for PC by stage at diagnosis and race have reached 98% among the selected cancer types [ 1 ]. Repeated use of single therapeutic agents may lead to undesirable and severe adverse effects; for example, most patients have difficulty accepting surgical castration therapy [ 3 , 4 ]. Worse still, with the development of the disease, ADT causes almost all patients to become less sensitive to androgens and progress to castration-resistant prostate cancer (CRPC) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The panel recommended medical over surgical castration during the epidemic, because they are associated with similar survival rates, 22 but medical castration is noninvasive and provided on an outpatient basis (R4.1). The use of longer‐acting medical castration agents may help to reduce the number of required hospital visits.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have reported the efficacy and tolerability of GnRH agonists as a first-line treatment for advanced PC and concluded that the survival rate, disease progression, and time to treatment failure are comparable between GnRH agonist therapy and orchiectomy [ 20 , 21 , 22 , 23 ]. Surgical castration is a simple and cost-effective outpatient procedure, while the advantage of medical castration is the avoidance of surgery [ 20 , 21 , 22 , 23 , 24 ]. In recent years, the rate of surgical castration has been reported to be less than 9% [ 24 ].…”
Section: Adtmentioning
confidence: 99%
“…Surgical castration is a simple and cost-effective outpatient procedure, while the advantage of medical castration is the avoidance of surgery [ 20 , 21 , 22 , 23 , 24 ]. In recent years, the rate of surgical castration has been reported to be less than 9% [ 24 ]. Although castration reduces serum testosterone levels by approximately 90%, 20–40% of dihydrotestosterone (DHT) remains in human PC tissue [ 25 , 26 , 27 ].…”
Section: Adtmentioning
confidence: 99%